HUBUNGAN ANTARA ORGANIZATIONAL CHARACTERISTICS, ENVIRONMENTAL CHARACTERISTICS DAN ENTREPENEURIAL ORIENTATION TERHADAP INOVASI TERBUKA SERTA KINERJA INOVASI (Survei pada UKM Provinsi Jawa Timur) - Irawan, Ari (FIA UB, 2020)
This study was conducted to determine the relationship between organizational characteristics, environmental characteristics and entrepreneurial orientation of startup companies in East Java to open innovation. The unit of analysis is startup owner or technopreneur owners in Malang City, Surabaya City and Kediri City as the research sample area. The number of respondents obtained was 102 business owners who use technology in their business practices. This type of research is explanatory quantitative research by describing the relationship between variables using the online version of the GSCA (Generalized Structured Component Analysis) software to analyze. The results of the study by comparing the values of t, showed that the three hypotheses were not supported by this study while the remaining 4 (four) hypotheses were supported.